Europe à la carte? : Swiss convergence towards European policy models in higher education and vocational education and training - Bieber, Tonia [Verfasser] (My University, 2010)
"In the last decade, European education has experienced far-reaching transformation through the international initiatives of the Bologna process in higher education (HE) and the Copenhagen process in vocational education and training (VET) for enhancing European cooperation. This study investigates the mostly underresearched effects of these initiatives on Switzerland to discern whether Swiss HE and VET policies have converged towards European models, and which mechanisms were influential. It combines research on Europeanization and convergence and uses process-tracing based on expert interviews and document analysis. Results reveal that Swiss HE policy strongly converged towards the Bologna model, while the development of a partial convergence of VET policy towards the model of the Copenhagen process can be observed. The study demonstrates the impact of domestic politics on shaping Europeanization effects and reconstructs the processes through which the initiatives took effect through transnational communication." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.4 Hochschulbildung; I 2.2 Europa; I 2.2.1 Westeuropa; EU-Bildungspolitik; Europäische Integration; Berufsbildung; Hochschulbildung; Bologna-Prozess; Konvergenz; Schweiz